Retroperitoneal robot‐assisted laparoscopic partial nephrectomy for posterior located renal tumours: Technique and early term outcomes. Issue 2 (8th December 2020) - Boga, Mehmet Salih; Ates, Mutlu
Abstract: Background: Traditionally, the trans‐peritoneal approach is preferred for robot‐assisted partial nephrectomy (RPN). However, retroperitoneal RPN (RP‐RPN) has recently become widespread because of the advantages of easier access to the hilum, ease dissection of posterior tumours, and lower probability of intra‐peritoneal organ injury. We aimed to present our initial experience of the RP‐RPN series in posteriorly located renal tumours. Methods: Twenty‐one patients were included in the study, who underwent RP‐RPN by a single surgeon between July 2019 and January 2020. RP‐RPN was carried out only in posteriorly located renal tumours with ischemic (on‐clamp) or zero ischemic (off‐clamp) techniques. Patients with solitary kidney and a history of previous retroperitoneal surgery in the lumbodorsal region were excluded from the study. Results: All cases completed without any operative complication and conversion to open or radical nephrectomy. Seven cases were completed as zero ischemic and 14 cases as ischemic technique. The mean operation time was 157.86 ± 64.24 minutes and estimated blood loss was 173.81 ± 136.84 mL. The mean warm ischemia time was 15.81 ± 12.42 minutes. Positive surgical margin observed in 4.8% of the patients. The mean length of stay was 3.33 ± 0.79 days. The mean estimated glomerular filtration rate (eGFR) change in the 3rd postoperative month was −3.71 ± 8.57 ml/min/1.73 m 2 (4.6%). Mean follow‐up period was 10.29 ± 4.86 months. New‐onset stage 3‐4 chronic kidney disease (eGFR < 60 m /min/1.73m 2 ) was not observed during the follow‐up period. Conclusion: RP‐RPN is a safe and feasible approach with acceptable oncological and functional results. We think that RP‐RPN can be applied as an alternative to the trans‐peritoneal approach for selected cases, especially in renal tumours with the posterior location.